The Impact of Maternity Length-of-Stay Mandates on the Labor Market and Insurance Coverage - Lindsay M. Sabik; Miriam J. Laugesen (SAGE Publishing, 2012)
To understand the effects of insurance regulation on the labor market and insurance coverage, this study uses a difference-in-difference-in-differences analysis to compare five states that passed minimum maternity length-of-stay laws with states that waited until after a federal law was passed. On average, we do not find statistically significant effects on labor market outcomes such as hours of work and wages. However, we find that employees of small firms in states with maternity length-of-stay mandates experienced a 6.2-percentage-point decline in the likelihood of having employer-sponsored insurance. Implementation of federal health reform that requires minimum benefit standards should consider the implications for firms of differing sizes.